The development of an expansive type special cement bonded investment powder for castings of non ferrous metals and alloys - Kutbay, I; Guler, K. A.; Cigdem, M. (TAYLOR & FRANCIS LTD, 2018)
An attempt has been made to develop an investment powder which expands significantly in the setting period to meet the solidification shrinkage of most metals and alloys. Investment powders consisting of tricalcium aluminate, quartz, various sulphate bearing compounds and a small amounts of controlling agents (additives) were used in the preparation of the block investment molds. A413 Al-Si (Etial 140) alloy was melted and poured in these molds to cast a test specimen of a special geometry. The preliminary results show that it is possible to produce dimensionally accurate castings by using expansive type investment powders. Samples cast into block investment molds prepared from ordinary non-expansive investment powder were smaller than the pattern size, while those poured into molds produced from expansive type powders were the same size or greater than the pattern size.
Keywords: Investment powder and casting; setting expansion; expansive mixtures; ettringite; ETTRINGITE FORMATION; CALCIUM-SULFATE; HEMIHYDRATE; HYDRATION; GYPSUM; SIZE; Metallurgy & Metallurgical Engineering